Association between recent U.S. northeast precipitation trends and Greenland blocking. (6th March 2022) - Simonson, Julia M.; Birkel, Sean D.; Maasch, Kirk A.; Mayewski, Paul A.; Lyon, Bradfield; Carleton, Andrew M.
Abstract: Since the early 2000s, the northeastern region of the United States (USNE) has received increased total annual precipitation along with more frequent extreme precipitation events. Although previous work has discussed the contribution to increased extreme precipitation from tropical cyclones, the large‐scale driver(s) of summer precipitation increases in the extratropics has received little attention. Here, we show that the summer‐season rainfall surpluses across the USNE are related to the increased frequency of atmospheric blocking over Greenland and the negative phase of the North Atlantic Oscillation. The occurrence of these patterns in summer has been previously connected with southward shifted storm tracks and wet conditions across the eastern North Atlantic. Over the USNE, the circulation shifts are also related to enhanced rainfall due to southerly wind anomalies and increased moisture transport into and vertical motion over the region. It is important to note that the current generation of climate models used for future projections is unable to reproduce the observed tendency towards increased atmospheric blocking over Greenland. Thus, clarifying the association between Greenland blocking and recent precipitation changes across the USNE may help inform future climate projections of summer season rainfall for the region. Abstract : While previous work has discussed the increase extreme precipitation in the northeastern United States (USNE) from tropical cyclones, the large‐scale driver of summer precipitation increases since the early 2000s has received little attention. We show that the summer‐season increase is related to the increased frequency of atmospheric blocking over Greenland and the negative phase of the North Atlantic Oscillation. This potential connection may help inform future climate projections of summer season rainfall for the region.